Optimalisasi Sarana dan Prasarana Pendidikan Berbasis Standar Nasional Pendidikan pada MTsS Sunanul Husna - Asti Cahya Dewi; Zahratul Munawwaroh; Aolia Lavianis; Najwa Amelia Zein; Nova Fadila (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2026)
Facilities and infrastructure are essential components in the provision of education, functioning to support the effectiveness of teaching and learning processes, student comfort, and the achievement of quality learning outcomes. In boarding-based Islamic schools (madrasah), facility needs become more complex due to the integration of formal academic curricula with religious instruction and a full residential system. The National Education Standards (SNP) serve as the national reference for the fulfillment of educational facilities in Indonesia; however, the standards do not specifically regulate boarding facilities, resulting in a gap in facility fulfillment among pesantren-based madrasah. This study aims to evaluate the suitability of educational facilities and infrastructure at MTsS Sunanul Husna, South Tangerang City, with the SNP and to identify inhibiting factors affecting the fulfillment of such standards. The research employed a qualitative case study design through observation, interviews, and documentation. Data analysis was conducted using interactive procedures, including data reduction, data display, and conclusion drawing. The findings indicate that academic facilities are categorized as adequate, with classrooms, teacher rooms, administrative offices, computer laboratories, and a UKS room available and functioning, although the library and student sanitation facilities require improvement. Boarding facilities such as dormitories, worship areas, and kitchen facilities are categorized as good, despite not being covered in the SNP. The study reveals that financial limitations, centralized authority at the foundation level, and the absence of national standards for boarding education represent the main inhibiting factors. The study implies the need for the formulation of facility standards specifically for boarding madrasah and for strengthened collaboration among the government, foundations, and communities in fulfilling educational infrastructure.